Estimates of the willingness to pay for locally grown tree fruits in Cusco, Peru - Blare, Trent; Donovan, Jason; del Pozo, Cesar (Cambridge University Press, 2019)
Urbanization, changes in the retail sector and economic growth in developing countries may offer new opportunities to build connections between urban consumers and nearby farmers. The design of strategies to build such connections will require deeper insights into the food preferences of urban consumers. This paper presents a choice experiment of the preference of locally grown apples, avocados and pears vis-à-vis nonlocal equivalents with 300 consumers in a traditional market in Cusco, Peru. Willingness-to-pay estimates are derived from a multinomal logit analysis. We found that consumers who are younger and more educated and those with young children tend to be willing to pay more for locally produced apples, avocados and pears. The paper concludes with a discussion on the implications of the research for advancing efforts to localize food systems in developing countries and opportunities for future research.